The usage of songs in the Arabic textbook and its effect on vocabulary recall : a case study at Sekolah Kebangsaan Batu Muda - Nurhalimah Siregar (Kulliyyah of Education, International Islamic University Malaysia, 2016)
In Malaysia, the Arabic language has been taught at primary and secondary schools. However, the majority of students lack interest in Arabic subjects due to factors such as the teaching method and the material. Consequently the Ministry of Education, Malaysia has included songs in the Arabic textbooks in order to enhance the students' interest. This study aimed to investigate the effect of songs in Arabic textbooks on students' vocabulary recall as well as their perception regarding the use of songs in learning Arabic. The study was carried at Sekolah Kebangsaan Batu Muda, Malaysia. A total of 45 students from year three at primary level participated in this study. They were split into an experimental and a control group. A quasi-experimental design was applied in this quantitative study, which consisted of a survey, and a pre-test and post-test protocol. The obtained data were analyzed quantitatively using simple descriptive statistical analysis consisting of frequencies and percentages and an Independent Sample t-Test. The findings from the survey demonstrated that students have a positive perception on the use of songs in learning Arabic. In addition, the findings from the pre-test and post-test showed a significant difference in the means gain score between the control and the experimental groups. The findings revealed that those who learn the text with songs are better in recalling the vocabulary than those who learn the same text without songs. The study, through its findings, intends to add to the growing body of knowledge regarding the use of songs in the Arabic classroom.